New trade in renewable resources and consumer preferences for diversity - Martin F. Quaas; Max T. Stöven (Kiel University, Department of Economics, 2014)
The literature on trade in renewable resources implicitly assumes that the traded resources are perfect substitutes. We model trade in renewable resources as stipulated not only by autarky price differences, but also by consumers' love of variety. We show that the love-of-variety effect enables welfare gains from trade even if total consumption decreases. Total consumption may decrease because the love of variety weakens the link between resource scarcity and demand. If consumers are willing to pay the rising prices for harvests from increasingly depleted stocks, trade liberalization may end in stock collapse. The love of variety may thus threaten variety.
Keywords: Q21; Q22; Q23; Q27; F18; 330; trade; environment; renewable resources; open access; love of variety